ICU: KNOWLEDGE OF NURSING TEAM ON INFECTION (Fiep Bulletin - online, 2014)
Objective: To evaluate the knowledge of nurses about risk of infection in a hospital intensive care unit. Methodology: an exploratory study with a qualitative approach, in the ICU of a regional hospital with a sample of ten professional nursing. Data were collected through a questionnaire in March 2013 after approval by the ethics committee of the Faculty Santa Maria number 253 075. For the analysis we used the technique of collective subject discourse proposed by Lefèvre and Lefèvre Results and Discussions: before questioning led to the following ideas: is an infection caused by microorganisms present in the hospital environment, invasive and non-washing hands, use standard precautions and aseptic technique when performing invasive procedures. Concluding remarks: research served to investigate the knowledge of nurses about the risks of patients acquiring an infection in the Intensive Care Unit and noted that the hospital staff has worked needs further clarification about the control of hospital infection.
Keywords: Intensive Care Units; Infection; Nursing Team; Knowledge.